COMPARATIVE EVALUATION OF A TWO-STAGE REFRIGERATION SYSTEM WITH FLASH INTERCOOLING USING DIFFERENT REFRIGERANTS - (:unkn) unknown (VINCA INST NUCLEAR SCI, 2020)
The aim of this study is to investigate the effect of low global warming potential refrigerants on the optimum intermediate pressure (P-OPT,P-int) and performance (COP) values of a refrigeration system with flash intercooling. For realize, the optimum operating parameters of system were determined in low temperature applications through a theoretical analysis according to the different refrigerants (R290, R404A, R407C, R507A, and R22). The theoretical modelling ofsystem is done by optimizing the intermediate pressure at given evaporation (T-E) and condensation (T-C) temperatures for selected refrigerants. After optimization, the maximized values of COP and Second law efficiency are computed from the predicted values of P-OPT,P-int. The linear regression method is then used to derive three correlations of P-OPT,P-int, maximum values of COP and Second law efficiency according to T-E and T-C Hence, the P-OPT,P-int values maximizing the system performance are found from various T-E and T-C values for each refrigerant. Due to calculations, increasing T-E and T-C cause the increase in P-OPT,P-int in low temperature applications. The R507A system has the highest P-OPT,P-int values and R22 system has the lowest P-OPT,P-int values. Although R22 system has slightly more efficient than R290 system, it is being phased out world-wide because of the risk of ozone depletion potential and global warming potential considerations. Therefore, it is important to evaluate the R22 replacement options. The R290 was discovered to have better performance than the R404A, R407C and R507A systems in terms of COPmax(1.81), global warming potential (11), and ozone depletion potential (0) when T-E and T-C are -35 degrees C and 40 degrees C.
Keywords: optimization; low temperature applications; COP; Second law efficiency; exergy loss; THERMODYNAMIC ANALYSIS; TEMPERATURE; PRESSURE